On source identification problem for a delay parabolic equation - Ashyralyev, Allaberen; Agirseven, Deniz (Nonlinear Analysis: Modelling and Control, 2014)
In the present study, the inverse problem of a delay parabolic equation with nonlocal conditions is investigated. The stability estimates in Hölder norms for the solution of this problem are established.
Keywords: delay parabolic equation; Banach spaces; positive operators; stability estimates; nonlocal conditions